Soluciones: Ejercicio 2 y 3
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 2) a)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 2) b)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 2) c)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 2) d)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) a) 
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) b)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) c)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) d)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) e)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) f)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) g)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) h)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) i)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 3) j)
f(x)=         x3 +       x2 +        x +            


f(x)=         (x-      )(x-      )(x-      )
Ejercicio 2) a)
Students who took this test also took :

Created with That Quiz — a math test site for students of all grade levels.